Implementation of Clinical Pharmacogenomics within a Large Health System: From Electronic Health Record Decision Support to Consultation Services. Issue 8 (20th July 2016) - Hicks, J. Kevin; Stowe, David; Willner, Marc A.; Wai, Maya; Daly, Thomas; Gordon, Steven M.; Lashner, Bret A.; Parikh, Sumit; White, Robert; Teng, Kathryn; Moss, Timothy; Erwin, Angelika; et al.
Abstract : The number of clinically relevant gene‐based guidelines and recommendations pertaining to drug prescribing continues to grow. Incorporating gene–drug interaction information into the drug‐prescribing process can help optimize pharmacotherapy outcomes and improve patient safety. However, pharmacogenomic implementation barriers exist such as integration of pharmacogenomic results into electronic health records (EHRs), development and deployment of pharmacogenomic decision support tools to EHRs, and feasible models for establishing ambulatory pharmacogenomic clinics. We describe the development of pharmacist‐managed pharmacogenomic services within a large health system. The Clinical Pharmacogenetics Implementation Consortium guidelines for HLA‐B*57:01 ‐abacavir, HLA‐B*15:02 ‐carbamazepine, and TPMT ‐thiopurines (i.e., azathioprine, mercaptopurine, and thioguanine) were systematically integrated into patient care. Sixty‐three custom rules and alerts (20 for TPMT ‐thiopurines, 8 for HLA‐B*57:01 ‐abacavir, and 35 for HLA‐B*15:02 ‐anticonvulsants) were developed and deployed to the EHR for the purpose of providing point‐of‐care pharmacogenomic decision support. In addition, a pharmacist and physician‐geneticist collaboration established a pharmacogenomics ambulatory clinic. This clinic provides genetic testing when warranted, result interpretation along with pharmacotherapy recommendations, and patient education. Our processes for developing these pharmacogenomic services and solutions for addressing implementation barriers are presented.